Educational Comic for Dental Caries Prevention in Kalijudan 1 Elementary School, Surabaya - Sosiawan, Agung; Bramantoro, Taufan; Putri Gofur, Aisyah Rachmadani; Devina, Dida; Kumala Dewi, Ni Nyoman Astari (Indonesian Journal of Dental Medicine, 2019)
Background: Dental caries is one of the dental and oral diseases, and it is caused by S. mutans. Almost all humans have dental caries, and it is a burden disease in Indonesia. The prevalence of dental caries is 79.1% worldwide, and the prevalence of child dental caries in Indonesia was 92.6% in 2018. Purpose: To promote child dental health awareness in children through an educational comic. Methods: Educational comics were distributed directly to students of Kalijudan Elementary School. Tools and materials of the empowerment program: Stationery, Laptop/computer, Application to layout the comic. There are 13 teachers and 30 students involved in this program. The students were given pre-test before learned about dental health from educational comics. After receiving health education materials from the comics books, they were given post-test to measure the increasement of health knowledge. Pre and post test data were analyzed with Paired-T test. Results: The pre-test and post-test results of the empowerment program at Kalijudan 1 elementary school were 12.3 and 13.6, respectively. There was a 1.3 point increase. The significance value was 0.000 (p-Value < 0.05). This means that there was a significant difference in children's knowledge levels before and after they read the comic. Conclusion: The result showed that children have learned that dental and oral health affects physical activities.